Study on Relationship between Cultural Intelligence Level and Academic Self-Efficacy of Undergrads - Vural, Mustafa; Peker, Alper Tunga (Asian Journal of Education and Training, 2019)
Aim of this study is to determine the relationship between cultural intelligence and academic self-efficacy of undergrads, in terms of different variables. A total of 169 people, (101 male/68 female) participated in the research. "Cultural Intelligence Scale" and "Academic Self-Efficacy Scale" were used in the research. Mann-Whitney U test was used for paired comparisons and Kruskal Wallis H test was used for multiple comparisons in the statistical analysis. Spearman correlation test was utilized to determine relationship between the scales. As a result of the research, it was determined that there were significant differences according to department of education and year of education variable and there were not significant differences according to other variables that are gender, place of accommodation and status of being interested in sports. When the relationship between academic self-efficacy and cultural intelligence was examined, it was concluded that there was a significant and positive relationship below the medium level.